The Relationship Between Lava Fountaining and Vent Morphology for the 2014–2015 Holuhraun Eruption, Iceland, Analyzed by Video Monitoring and Topographic Mapping - Witt, Tanja; Walter, Thomas R.; Müller, Daniel; Guðmundsson, Magnús T.; Schöpa, Anne (Frontiers in Earth Science, 2018)
Fissure eruptions are associated with lava fountains which often show complex distinct venting activity, in pulsating form, and the development of characteristic morphologic expressions such as scoria or spatter cones. Most morphological studies are based on observations of old structures and are not related to direct observations and systematic records of vents activity, which are rare. The 2014 - 2015 Holuhraun eruption site, Iceland, offered an exceptional opportunity to study with unprecedented details the location and evolution of those cones and their relationship to the venting dynamic. Here we analyse records from lava fountains activity at distinguished vents, captured during the 2014-2015 Holuhraun eruption, and compare them with the developing morphology of spatter cones. We conducted a fieldwork mapping project combining Terrestrial Laser Scanning (TLS) and Unmanned Aerial Vehicle (UAV) aerophoto techniques to characterize the cone morphologies. We recorded videos of the eruption and used edge detection and particle image velocimetry to estimate venting heights and particle velocities. We find that at those locations where spatter cone morphology developed the strongest, the highest lava fountains and larger ejection velocities were recorded, already at the very first days of the eruption. Instead, those sites that finally developed moderate or weak morphologies are also identified as less active lave fountain locations during the early stage of the eruption. The comparison of our topographic datasets shows that spatter cones remain similar in shape but increase in size as the eruption progress. In addition, we suggest that the observed changes in morphology may affect lava ponding in the crater, which in turn is strongly affecting eruption heights. Our results improve the general understanding of landscape evolution at rift zones, and demonstrate the close relationship between the cone morphology and the lava fountain activity at the onset of an eruption.